Pengaruh Asal Bahan Stek dan Jenis Zat Pengatur Tumbuh (Zpt) pada Pertumbuhan Stek Daun Lidah Mertua (Sansevieria Trifasciata) - Pienyani Rosawanti (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This research aims to study the growth response of plant leaf cuttings mother in-law’s tongue (Sansevieria parva) origin of cuttings and various plant growth regulator treatment. Research was using complete randomized block design (RAKL) with 6 replications. The first factor was the origin of cuttings, i.e. the top/tip leaves, the middle leave, and the bottom/leaves base. The second factor was the various plant growth regulator (PGR) treatment i.e. onion extracts, water coconut and Rootone-F. Parameters observed and measured is the experiment root length, number of roots, root wet weight and root dry weight. The results showed that plant growth regulator treatment significant effect on root length, number of roots, root wet weight, and root dry weight. The treatment combination of origin of cuttings and synthetic plant growth regulator by cutting material from the middle to give the best results on the number of root and root wet weight.